Impact of Middle School Student Energy Monitoring Activities on Climate Change Beliefs and Intentions - Christensen, Rhonda; Knezek, Gerald (School Science and Mathematics, 2018)
The Going Green! Middle Schoolers Out to Save the World project aims to direct middle school students' enthusiasm for hands-on activities toward interest in science and other STEM areas while guiding them to solve real-world problems. Students in this project are taught by their teachers to use energy monitoring equipment to audit standby power consumed by electronic devices in their homes and communities. Major findings were: (a) Beliefs in climate change increased more for students in the treatment than comparison group, pre to post; and (b) For girls there was a larger positive impact on climate change beliefs than for boys. These and additional findings presented in this paper provide evidence that a hands-on engaged-learning curriculum can have a positive influence on climate change beliefs and intentions and strengthen the association between the two constructs.
Keywords: active learning; climate change; hands-on learning; middle school students